The Influence of Practical Facilities on the Quality of Learning at State Vocational Schools - Kristin Handayani; Widya Kusumaningsih; I Made Sudana (Universitas Negeri Semarang, 2025)
Vocational High Schools (SMK) play a crucial role in preparing a competent workforce ready to meet industrial challenges. However, the implementation of practicum methods faces various obstacles, particularly in terms of limited facilities. This study quantitatively examines the impact of practicum facilities on learning quality at SMK Negeri in Blora Regency. Through a data-driven approach, it aims to provide concrete recommendations for policymakers in enhancing vocational education effectively and sustainably. Using a quantitative correlational and ex post facto research approach, the study involved 383 vocational school teachers, with a sample of 196 respondents. Data was collected through questionnaires and analyzed for validity, reliability, normality, linearity, multicollinearity, and heteroscedasticity. The descriptive analysis shows that 20.92% of respondents rated the facilities as excellent, 36.73% as good, 26.53% as adequate, 11.22% as poor, and 4.59% as very poor The findings indicate that 85.7% of learning quality variation is influenced by practicum facilities, with an effective contribution of 84.54% and a relative contribution of 98.42%.. These results highlight the significant role of practicum facilities in improving learning outcomes and ensuring graduates' readiness for industrial demands. Enhancing these facilities is essential for the effectiveness and sustainability of vocational education